THE EFFECT OF COOPERATIVE PLAY PUZZLE THERAPY ON SOCIAL INTERACTION SKILLS IN CHILDREN WITH INTELLECTUAL DISABILITIES - Putri Mayang Sari putri; David Arif Faizal (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Intellectual disability is one of the categories of children with special needs who require specialized care and educational services to support their growth and development. Social interaction skills in children with intellectual disabilities often do not develop optimally, resulting in difficulties in social adaptation, independence, and two-way communication with peers and others. To analyze the effect of Cooperative Play Puzzle therapy on the social interaction skills of children with intellectual disabilities. Methods: This study employed a quasi-experimental design using a one-group pretest-posttest approach. The research was conducted at SLB Negeri Baturaja. Participants were selected using purposive sampling, and social interaction skills were assessed using an observational checklist. A total of 15 children with intellectual disabilities participated in the study. The research was conducted from November 10 to November 22, 2025. The study procedures consisted of a pretest to assess social interaction skills, followed by Cooperative Play Puzzle therapy administered in three sessions, each lasting 30 minutes, and concluded with a posttest assessment. Data were analyzed using the Wilcoxon Signed-Rank Test to determine the effect of Cooperative Play Puzzle therapy on social interaction skills. Before the intervention, most participants demonstrated moderate social interaction skills, accounting for 8 respondents (53.3%). After receiving Cooperative Play Puzzle therapy, nearly all participants showed improved social interaction skills, with 12 respondents (80%) demonstrating good social interaction abilities. The Wilcoxon Signed-Rank Test revealed a p-value of 0.004 (p < 0.05), indicating a statistically significant improvement in social interaction skills following the intervention. Cooperative Play Puzzle therapy significantly improves social interaction skills in children with intellectual disabilities. This therapy can be considered an effective intervention to enhance social development and peer interaction among children with intellectual disabilities.